2010
DOI: 10.1111/j.1440-1746.2010.06249.x
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of overlaps between GERD, FD and IBS and impact on health‐related quality of life

Abstract: Overlaps among GERD, FD and IBS were common and worsened HR-QOL in Japanese general population.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

15
100
0
1

Year Published

2011
2011
2022
2022

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 197 publications
(116 citation statements)
references
References 42 publications
(82 reference statements)
15
100
0
1
Order By: Relevance
“…[10][11][12][13] In healthy adults, the prevalence of IBS using the Rome III diagnostic questionnaire was reported to be approximately 10% to 15%. [23][24][25] The Rome III classification is based on the symptom-based diagnostic criteria which is not explained by pathologically and endoscopically based disorders. Regarding the Rome III classification, the duration for the diagnosic criteria originates at 6 months prior to clinical presentation, and diagnosis and must be currently active for 3 months.…”
Section: Discussionmentioning
confidence: 99%
“…[10][11][12][13] In healthy adults, the prevalence of IBS using the Rome III diagnostic questionnaire was reported to be approximately 10% to 15%. [23][24][25] The Rome III classification is based on the symptom-based diagnostic criteria which is not explained by pathologically and endoscopically based disorders. Regarding the Rome III classification, the duration for the diagnosic criteria originates at 6 months prior to clinical presentation, and diagnosis and must be currently active for 3 months.…”
Section: Discussionmentioning
confidence: 99%
“…According to those reports, 25 % of FD patients also show GERD symptoms [9]. Thus, such overlap will almost certainly be encountered by physicians in a clinical setting.…”
Section: Prognosis and Complicationsmentioning
confidence: 99%
“…Our previous study showed that overlaps among GERD, FD, and IBS were common, accounting for 47% of GERD, 48% of FD, and 34% of IBS patients (9). Patients with GERD, FD, or IBS reported significantly poor health-related quality of life (HR-QOL), and the HR-QOL was markedly worse in the overlapping condition as compared with GERD, FD, and IBS alone.…”
Section: Introductionmentioning
confidence: 99%
“…Patients with GERD, FD, or IBS reported significantly poor health-related quality of life (HR-QOL), and the HR-QOL was markedly worse in the overlapping condition as compared with GERD, FD, and IBS alone. In particular, the physical component summary for overlapping GERD and mental component summary for overlapping IBS were poor (9). Therefore, physicians should pay attention to the overlapping of functional GI disorders.…”
Section: Introductionmentioning
confidence: 99%